Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes-group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A. (Zootaxa, 2016)
Coeliccia matok sp. nov. (holotype male from Borneo, Sarawak, Samarahan Division, peat swamp forest at old UNIMAS campus, 25 ii 2008, to be deposited in BMNH) and Coeliccia paludensis sp. nov. (holotype male from Borneo, Kalimantan Tengah, peat swamp forest in ex Mega Rice Project Block E, 18 vi 2012, in RMNH) are described from Borneo. The two new species are apparently confined to peat swamp forest (C. paludensis) or largely confined to peat swamp forest and related forest formations (C. matok). Coeliccia macrostigma Laidlaw is redescribed and all available information on it is summarised. Additional terminology for characters of the prothorax in Coeliccia species is introduced. Distribution maps are given for all three species considered.